1995
DOI: 10.1016/0735-1097(95)80004-z
|View full text |Cite
|
Sign up to set email alerts
|

Exercise echocardiography is an accurate and cost-efficient technique for detection of coronary artery disease in women

Abstract: Exercise echocardiography is more specific than exercise electrocardiography for diagnosis of coronary artery disease in women and is a cost-effective approach to the diagnosis of coronary artery disease because of the avoidance of inappropriate angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
77
2
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(84 citation statements)
references
References 28 publications
2
77
2
3
Order By: Relevance
“…18,19 In the present study specificity of ECG stress test in women was only 50% ( Table 2). The advantage of stress echocardiography over ECG stress test was more obvious in hypertensive women than in hypertensive men.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…18,19 In the present study specificity of ECG stress test in women was only 50% ( Table 2). The advantage of stress echocardiography over ECG stress test was more obvious in hypertensive women than in hypertensive men.…”
Section: Discussioncontrasting
confidence: 56%
“…The other study that included patients with no defined blood pressure, revealed that exercise echo was also slightly more sensitive than dobutamine (76% vs 72%) but less specific (94% vs 97%). 19 In this study the exercise in comparison to dobutamine echocardiography was associated with the larger extent of the left ventricular wall motion abnormalities. This factor may facilitate recognition of abnormal left ventricular wall motion during echocardiography.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This gender difference remains even when combining the interpretation of ST-segment deviation with exercise time and exercise induced symptoms into the Duke Treadmill Score (DTS) [11,12]. These difficulties posed on the clinical determination of CAD probability have led to speculation that stress imaging approaches may be an efficient initial alternative to exercise ECG in women [13], however few data are available to support this approach.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that exercise [7][8][9] and dipyridamole echocardiography 10 may be better noninvasive tests for diagnosis of CAD in women. Dobutamine stress echocardiography (DOBE) is increasingly used for detection of CAD, 11,12 but its diagnostic accuracy has not been defined in women.…”
Section: Introductionmentioning
confidence: 99%